The Roman merchant ship sail plan: steering a windward passage. - Davey, Christopher J. (Buried History: The Journal of the Australian Institute of Archaeology, 2019)
Two papers about the introduction of the spritsail during the Roman period in previous editions of Buried History are updated with additional references and hypotheses. A revised interpretation of Problem 7 in the Aristotelian corpus Mekhanika is given but the foregoing proposition that the introduction of spritsails made sailing to windward routine for Roman merchant sailing ships is retained. It is suggested that extremes of wind strength were the main inhibitors of windward sailing because it reduced boat speed, which in turn diminished lateral resistance and increased leeway.